Involvement of Calcium and Calmodulin in Nitric Oxide-Regulated Senescence of Cut Lily Flowers - Zhang, Jing; Fang, Hua; Huo, Jianqiang; Huang, Dengjing; Wang, Bo; Liao, Weibiao (Frontiers in Plant Science, 2018)
Both nitric oxide (NO) and calcium ion (Ca2+)/calmodulin (CaM) have been shown to regulate the senescence of cut flowers. However, not much is known about the crosstalk between NO and Ca2+/CaM during the senescence of cut flowers. In this study, cut Oriental × Trumpet hybrid lily ‘Manissa’ were used to investigate the roles and relationship between NO and Ca2+/CaM during postharvest freshness. The results show that the effects of CaCl2 or NO donor SNAP on the vase life, maximum flower diameter and hours until full opening were dose dependent, with an optimum concentration of 20 mM CaCl2 or 100 µM SNAP. However, Ca2+ chelators EGTA or BAPTA/AM, Ca2+ channel inhibitors LaCl3 or nifedipine and CaM antagonists W-7 or TFP inhibited the promotion of SNAP. SNAP applied alone significantly increased the endogenous Ca2+/CaM contents in cut lily flowers, while EGTA, BAPTA/AM, LaCl3, nifedipine, W-7 and TFP decreased the advancement of SNAP. In addition, the SNAP-induced Ca2+-ATPase activity was more than twice as much as the control, but EGTA, BAPTA/AM, LaCl3, nifedipine, W-7 and TFP also reversed the enhancement. Moreover, EGTA, BAPTA/AM, LaCl3, nifedipine, W-7 and TFP prevented the SNAP-induced upregulation of gene expression of CaM, CBL1, and CBL3, which is associated with calcium signaling pathway. Overall, these results suggest that Ca2+/CaM may function as downstream molecules in NO-regulated senescence of cut flowers.